Analysis Of The Effectiveness Of Psychological Support Programs For Civilians During And After The War In Lebanon And Artsakh - Ghazarian, Mary; Lachinyan, Lilit (Զանգակ հրատ.)
This article presents the psychological impacts of war on human life, especially on children in areas of conflict and war. The study offers various research on the short-term and long-term effects of war and violence on individuals, especially children. It sheds light on the presence and quality of psychological support offered to civilians during the war and the post-war period in Lebanon and Artsakh. It investigates the presence of programs that prepare individuals to be resilient during pre-armed conflict times in the era of peace. The paper offers recommendations that will lead to the placement of emotional intelligence and social-emotional learning programs that help develop children's self-awareness, offer them self-regulation tools and allow them to remain motivated at times of peace and war. The post-conflict programs will help civilians reduce anxiety and the impact of stress to overcome several psychological problems caused by wars in the population during times of peace and post-conflict
Keywords: Psychology